Flavonoids from Plinia cauliflora (Mart.) Kausel (Myrtaceae) with antifungal activity. Issue 17 (2nd September 2019) - Souza-Moreira, Tatiana M.; Severi, Juliana A.; Rodrigues, Edvânio Ramos; de Paula, Mayara Ivani; Freitas, Jolindo A.; Vilegas, Wagner; Pietro, Rosemeire C. L. R.
Abstract: Plinia cauliflora is a plant species with edible fruits but its chemical composition is not totally known yet although former studies showed its potential as antifungal agent. This work aimed the chemical analysis of the leaves, the activity against fungi species and evaluated cytotoxicity. Extract was obtained with 70% ethanol. An ethyl acetate fraction was obtained and glycosylated quercetin and myricetin were isolated. Samples were tested against Candida species, dermatophytes and entomopathogenic fungi. Cytotoxicity was evaluated against fibroblast cells. Extract showed good activity against C. albicans (minimum inhibitory concentration at 156 μg/mL), C. parapsilosis (78 μg/mL), C. krusei (19 μg/mL), Trichophyton rubrum (78 μg/mL) and Microsporum canis (156 μg/mL). Isolated compounds were more active against C. krusei and T. rubrum . The extract, which was the more active sample, demonstrated low cytotoxic effect and encourage more studies against rising non- albicans species and dermatophyte T. rubrum . Abstract :